2017
DOI: 10.1002/ped4.12011
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of sound‐processing strategies on tonal language cochlear implant users: A systematic review

Abstract: Importance: Contemporary cochlear implants (CIs) are well established as a technology for people with severe-to-profound sensorineural hearing loss, with their effectiveness having been widely reported. However, for tonal language CI recipients, speech perception remains a challenge: Conventional signal processing strategies have been demonstrated to possibly provide insufficient information to encode tonal cues, and CI recipients have exhibited considerable deficits in tone perception.Thus, some tonal languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…So far, many studies have documented the deficits in tone perception and production in prelingually deafened children with CIs (Y. Chen & Wong, 2017; Ciocca, Francis, Aisha, & Wong, 2002; Han et al, 2007; Liu, Peng, Zhao, & Ni, 2017; Mao & Xu, 2017; Peng, Weiss, Cheung, & Lin, 2004; Tan, Dowell, & Vogel, 2016; Xu et al, 2004, 2011; Xu & Zhou, 2011). In studies evaluating music perception in CI recipients, researchers have found that, although CI users perform relatively well on rhythm perception such as rhythm pattern recognition and rhythm discrimination, they show evident deficiency in pitch-related tasks such as pitch discrimination, pitch ranking, melody contour identification, and so forth (Cooper, Tobey, & Loizou, 2008; Galvin, Fu, & Nogaki, 2007; Gfeller et al, 2007; Limb & Rubinstein, 2012; McDermott, 2004; Scorpecci et al, 2012).…”
Section: Pitch Perception and Production In Cochlear Implant Usersmentioning
confidence: 99%
“…So far, many studies have documented the deficits in tone perception and production in prelingually deafened children with CIs (Y. Chen & Wong, 2017; Ciocca, Francis, Aisha, & Wong, 2002; Han et al, 2007; Liu, Peng, Zhao, & Ni, 2017; Mao & Xu, 2017; Peng, Weiss, Cheung, & Lin, 2004; Tan, Dowell, & Vogel, 2016; Xu et al, 2004, 2011; Xu & Zhou, 2011). In studies evaluating music perception in CI recipients, researchers have found that, although CI users perform relatively well on rhythm perception such as rhythm pattern recognition and rhythm discrimination, they show evident deficiency in pitch-related tasks such as pitch discrimination, pitch ranking, melody contour identification, and so forth (Cooper, Tobey, & Loizou, 2008; Galvin, Fu, & Nogaki, 2007; Gfeller et al, 2007; Limb & Rubinstein, 2012; McDermott, 2004; Scorpecci et al, 2012).…”
Section: Pitch Perception and Production In Cochlear Implant Usersmentioning
confidence: 99%
“…Normal hearing (NH) listeners of tonal languages can use pitch cues to distinguish lexical tones robustly even when acoustic signals are degraded by environmental noise, low-fidelity playback, human speech production variability, etc. In contrast, for most cochlear implant (CI) recipients, lexical tone perception is still challenging (Lu et al, 2022 ), and performance varies significantly across recipients and in environments (Chang et al, 2016 ; Liu et al, 2017 ; Mao and Xu, 2017 ; Li et al, 2018 ; Tang et al, 2019 ). This is perhaps unsurprising given CI recipients' weaker and more variable abilities to extract pitch cues from acoustic signals (Tao et al, 2015 ; Mok et al, 2017 ; Vandali et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pitch information is not adequately coded in the contemporary envelope-based speech processing strategies in which fixed-rate electrical stimulations delivered to a small number of CI electrodes result in poor pitch perception in CI users ( Wilson and Dorman, 2008 ; Xu and Zhou, 2011 ). At present, numerous studies have reported that there are considerable deficits in Mandarin tone recognition for CI children (see Tan et al, 2016 ; Chen and Wong, 2017 ; Liu et al, 2017 for reviews). For example, Zhou et al (2013) and Mao and Xu (2017) reported that CI children achieved Mandarin tone recognition of 67.3 to 82.3% correct, whereas their normal-hearing (NH) counterpart obtained > 95% correct.…”
Section: Introductionmentioning
confidence: 99%